Enhancing Value and Agricultural Use of Shiitake Mushroom Byproducts: Investigating Biodegradable Active Compounds - , Aayushi Mainali; , Anshul Pandey; , Munish Kaundal (Archives of Current Research International, 2025)
The edible fungus Shiitake mushroom the most significant edible fungi that has been Lentinus edodes is one of extensively cultivated globally and retains very high economic value as well as nutritional value and continues to maintain particular significance in Asia such as Japan, China and Korea because Shiitake mushrooms have been used as an the ingredient in food and medicine for centuries. China produces the 22% of world's mushroom production, and most mushrooms are produced in the world. Shiitake is gaining popularity in India and its post-market is also growing due to its high-value nutrient content and health benefits. Enormous cultivation methodology such as by-products are generated through mushroom spent mushroom substrate (SMS) and stipes along with non-commercial mushrooms. Each kilogram of fungi produces 5kg of waste stream, and this waste stream is hemicellulose and lignin. Edible mushroom production rich in cellulose, generates by-product materials that includes polysaccharides, proteins, and immunomodulatory bioactive substances. SMS is antimicrobial, antioxidant the key for sustainable mushroom cultivation. When SMS is integrated into nutritional waste supplements by the food industry and thereby provides a valuable management system. Spent mushroom substrate (SMS) has a mixture of organic and inorganic matter, which is used to produce biogas and biochar products that enhance soil quality and sequester atmospheric carbon dioxide. Shiittake Mushroom Waste Materials their Characteristics, Storage, nutrition and Its Different Sustainable Utility explores how Shiitake mushroom waste may be used in a variety of agricultural and mechanical applications while maintaining its environmental benefits as a waste management and recovery material.